The constraints of indigenous community (Jungle people/Orang Rimba) in accessing formal education - Alfian Alfian (Jurnal Pendidikan dan Konseling (JPDK), 2023)
The issue regarding a unique isolated indigenous community (Orang Rimba/ Jungle people) in Jambi, Indonesia is the dispossession and alienation of their land and resources as a result of the expansion of palm oil (farming industry) and illegal logging. Consequently, the Orang Rimba has been forced to move to other forested areas as their settlements and resources for living become scarce. Besides moving to the other forested area, those indigenous communities have to live near the mainstream community. However, one of the biggest problem for those who choose to live in the mainstream community is that they cannot speak the language, they cannot read, write, and they do not know anything about modern world, such as, education, politics, money, clothes, vehicle, etc. As a result, this will not enable them to have “a highly integrated, well-functioning society”. Thus, Education is one way to develop them. However, they have many constraints in accessing formal education. Some of the constraints are categorized into external (unavailability of school near their area, teacher, and curriculum) and internal constraints, such as Melangun- leaving the place where indigenous community live, school uniform and refusal to go to school). These constrains in accessing formal education can be solved by building partnership (government, NGO, and Palm Plantation Company) and alternative education. The further research to find out the suitable education for orang Rimba should be conducted.